Irradiation-injured brain tissues can self-renew in the absence of the pivotal tumor suppressor p53 in the medaka ( Oryzias latipes ) embryo - Yasuda, Takako (Oxford University Press, 2016)

(untitled) (J Radiat Res)
The tumor suppressor protein, p53, plays pivotal roles in regulating apoptosis and proliferation in the embryonic and adult central nervous system (CNS) following neuronal injuries such as those induced by ionizing radiation. There is increasing evidence that p53 negatively regulates the self-renewal of neural stem cells in the adult murine brain; however, it is still unknown whether p53 is essential for self-renewal in the injured developing CNS. Previously, we demonstrated that the numbers of apoptotic cells in medaka ( Oryzias latipes ) embryos decreased in the absence of p53 at 12–24 h after irradiation with 10-Gy gamma rays. Here, we used histology to examine the later morphological development of the irradiated medaka brain. In p53-deficient larvae, the embryonic brain possessed similar vacuoles in the brain and retina, although the vacuoles were much smaller and fewer than those found in wild-type embryos. At the time of hatching (6 days after irradiation), no brain abnormality was observed. In contrast, severe disorganized neuronal arrangements were still present in the brain of irradiated wild-type embryos. Our present results demonstrated that self-renewal of the brain tissue completed faster in the absence of p53 than wild type at the time of hatching because p53 reduces the acute severe neural apoptosis induced by irradiation, suggesting that p53 is not essential for tissue self-renewal in developing brain.